Trial Proving in Electronic Criminal Case Trial Based On the Dignified Justice Perspective - Novritsar Hasintongan Pakpahan; Teguh Prasetyo; Erny Herlin Setyorini; Yovita Arie Mangesti (Ius Poenale, 2022)
Trial proving in Indonesia has always been limited to Criminal Procedural Law and other regulations. Following the recent development of electronic criminal case trials, there has not been any precise regulation aside from Supreme Court Regulation 4 of 2020. The contradiction between KUHAP and Supreme Court Regulation causes problems, especially regarding trial proving. The purpose of the paper is to provide a legal solution to the problem of the legal emptiness regarding the regulation of trial proving in electronic criminal case trials from the perspective of Dignified Justice that will provide advantageous, responsive, and adaptive justice towards the needs of the community. The methodology of this research is based on normative research. The normative research methods used in this research are the statute approach, normative approach, and comparative approach. The result showed there shouldn't be a conflict between the effect of KUHAP and Supreme Court Regulation. Yet, the regulation of trial proving in an electronic criminal trial should be regulated at a statute level.